96.2k views
16 votes
What is the solution to the system:
-18x + 6y = -6
-24 + 6y = -18

User Carmenza
by
5.3k points

1 Answer

4 votes

Answer:

The solution of this system is (2, 5)

Explanation:

Negate each term of the 2nd equation. We get:

-18x + 6y = -6

24x - 6y = 18

Combining like terms, we get

6x = 12, from which we know that x = 2.

Substituting 2 for x in the first equation, we get

-18(2) + 6y = -6, which simplifies to 6y = 30. Thus, y = 5.

The solution of this system is (2, 5)

User Arda Basoglu
by
4.9k points